Adjuvant Therapy Using Mistletoe Containing Drugs Boosts the T-Cell-Mediated Killing of Glioma Cells and Prolongs the Survival of Glioma Bearing Mice. (27th August 2018) - Schötterl, Sonja; Huber, Stephan M.; Lentzen, Hans; Mittelbronn, Michel; Naumann, Ulrike
Abstract : Viscum album L. extracts (VE) are applied as complementary cancer therapeutics for more than one century. Extracts contain several compounds like mistletoe lectins (ML) 1-3 and viscotoxins, but also several minor ingredients. Since ML-1 has been described as one of the main active components harboring antitumor activity, purified native or recombinant ML-1 has been also used in clinical trials in the last years. The present study examined and compared the immunoboosting effects of three ML-1 containing drugs (the extract ISCADOR Qu, the recombinant ML-1 Aviscumine, and purified native ML-1) in the context of the T-cell mediated killing of glioma cells. Additionally we examined the possible underlying T-cell stimulating mechanisms. Using cocultures of immune and glioma cells, a PCR-based microarray, quantitative RT-PCR, and an antibody-based array to measure cytokines in blood serum, immunosupporting effects were determined. A highly aggressive, orthotopic, immunocompetent syngeneic mouse glioma model was used to determine the survival of mice treated with ISCADOR Qu alone or in combination with tumor irradiation and temozolomide (TMZ). Treatment of glioblastoma (GBM) cells with ISCADOR Qu that contains a high ML concentration, but also viscotoxins and other compounds, as well as with Aviscumine or native ML-1, enhanced the expansion of cancer cell-specific T-cells as well as T-cell-mediated tumor cell lysis, but to a different degree. In GBM cells all three ML-1-containing preparations modulated the expression of immune response associated genes. In vivo, subcutaneous ISCADOR Qu injections at increasing concentration induced cytokine release in immunocompetent VM/Dk-mice. Finally, ISCADOR Qu, if applied in combination with tumor irradiation and TMZ, further prolonged the survival of glioma mice. Our findings indicate that ML-1 containing drugs enhance anti-GBM immune responses and work in synergy with radiochemotherapy. Therefore, adjuvant mistletoe therapy should be considered as an auspicious treatment option for glioma patients.